Different manifestations of class II division 2 incisor retroclination and their association with dental anomalies - Pereira, Pedro Mariano (2014)
Notice: this is the author’s version of a work that was accepted for publication in Journal of Orthodontics. Changes resulting from the publishing process may not be reflected in this document. Final version available in Journal of Orthodontics. Vol. 40, Issue 4, (December 2013). DOI 10.1179/1465313313Y.0000000067.